2016
DOI: 10.1002/gps.4486
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and cognitive function in older adults: which aspect of perceived stress is important?

Abstract: In older adults, especially perceived self-efficacy showed independent associations with a broad range of cognitive functions. Perceived self-efficacy might be an important factor in reducing stress and the prevention of cognitive decline. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 25 publications
10
56
1
2
Order By: Relevance
“…First of all, we found that greater psychological stress was significantly related to lower performance in verbal abilities and processing speed. This is in line with prior evidence suggesting that psychological (and also physiological) stress impairs cognitive functioning (e.g., memory and processing speed) in old age [28, 32, 33]. Furthermore, we found that higher education, a higher cognitive level of the job, and greater engaging in leisure activities were related to better performance in the cognitive performance measures.…”
Section: Discussionsupporting
confidence: 80%
“…First of all, we found that greater psychological stress was significantly related to lower performance in verbal abilities and processing speed. This is in line with prior evidence suggesting that psychological (and also physiological) stress impairs cognitive functioning (e.g., memory and processing speed) in old age [28, 32, 33]. Furthermore, we found that higher education, a higher cognitive level of the job, and greater engaging in leisure activities were related to better performance in the cognitive performance measures.…”
Section: Discussionsupporting
confidence: 80%
“…Heightened levels of stress, both subjective and objective, have been reported in observational studies to be associated with executive dysfunction across multiple populations, including individuals with disabilities, individuals exposed to trauma, older adults, and healthy adult controls (12,(20)(21)(22)(23)(24)(25). Greater perceived stress, a measure of subjective stress in response to external stressors, has been found to be associated with poorer cognitive functioning including attentional control, processing speed, and working memory (20,22). Likewise, objective indices of stress (e.g., life events, parenting a child with a disability) have been associated with similar aberrations in executive function across diverse populations (24,25).…”
Section: Stress and Cognitive Functionmentioning
confidence: 99%
“…Likewise, objective indices of stress (e.g., life events, parenting a child with a disability) have been associated with similar aberrations in executive function across diverse populations (24,25). These objective stressors have been found to be associated with cognitive dysfunction (including poorer episodic memory) (26), decreased well-being (27), poor mental health (28,29), as well as changes to biological mechanisms, such as dampened cortisol-awakening-responses (30)(31)(32), and alterations to the neural structures that underlie stress-related responses (21,22,33).…”
Section: Stress and Cognitive Functionmentioning
confidence: 99%
“…Heightened levels of stress, both subjective and objective, have been reported in observational studies to be associated with executive dysfunction across multiple populations, including individuals with disabilities, individuals exposed to trauma, older adults, and healthy adult controls (18,(24)(25)(26)(27)(28)(29).…”
Section: Stress and Cognitive Functionmentioning
confidence: 99%
“…Greater perceived stress, a measure of subjective stress in response to external stressors, has been found to be associated with poorer cognitive functioning including attentional control, processing speed, and working memory (24,26). Likewise, objective indices of stress (e.g., life events, parenting a child with a disability) may prompt similar aberrations in executive function across diverse populations (28,29).…”
Section: Stress and Cognitive Functionmentioning
confidence: 99%